Características de refugios de algunas especies de murciélagos en la cuenca alta del río Itaya, Loreto, Perú (UNED Research Journal, 2013)
Roost characteristics for 14 bat species of the Itaya river headwaters, Loreto, Peru.This study presents information about bat roosts and their users in the Itaya River headwater, approximately 80km Southwest of Iquitos City (Northeastern Peru). This study was made from May to October of 2008. We established four sampling localities which were evaluated through intensive searches of potential roosts in line transects. The sampling effort covered 98km and we recorded 21 roosts corresponding to six types. The most common roost type was the tree cavity (n=12), followed by bark (n=5), furled leaf (n=1), termite nest (n=1), tent (n=1) and eroded dirt (n=1): this last type is described here for the first time. We identified 14 species representing 12 genera and 4 families (Phyllostomidae, Thyropteridae, Furipteridae and Emballonuridae). Roosts had 1-3 species, but most harbored only one. Phyllostomidae (except Choeroniscus minor), Thyropteridae and Furipteridae used protected sites such as tree cavities, termite nests, furled leaves and tents, while Emballonuridae were often found in exposed sites. KEY WORDSRoosts, Bats, Itaya River, Loreto, Peru